2018
DOI: 10.5296/ijhrs.v8i3.13190
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction of Library Staff: A Study Based on University Libraries in Sri Lanka

Abstract: Library of a university considered as an important entity of a university and employees of the library have a key role to play in disseminating knowledge to the academic clientele in the university. This study conducted to comprehensively investigate the job satisfaction of employees as the main objective and followed by identifying the main factors and finally to provide suggestions to overcome the dissatisfaction level of jobs of staff serving in respective universities. Study sample comprised with 510 respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…A high percentage (67%) of the participants indicated that they were not satisfied with the prevailing promotion scheme. This finding conformed to the results found in studies of Ranaweera and Li (2018), Wanasinghe (2019), Kumar (2018), Sambo (2014), Farajpahlou andAkhshik (2008) and, Khan and Ahmed (2013).…”
Section: Theme 3: Promotionssupporting
confidence: 91%
See 2 more Smart Citations
“…A high percentage (67%) of the participants indicated that they were not satisfied with the prevailing promotion scheme. This finding conformed to the results found in studies of Ranaweera and Li (2018), Wanasinghe (2019), Kumar (2018), Sambo (2014), Farajpahlou andAkhshik (2008) and, Khan and Ahmed (2013).…”
Section: Theme 3: Promotionssupporting
confidence: 91%
“…On the other hand, Ranaweera and Li (2018) surveyed university library employees in Sri Lanka and observed that they were fairly Journal of the University Librarians Association of Sri Lanka, Vol.24, Issue 2, June 2021, 88-119 DOI: http://doi.org/ 97 satisfied with their jobs. Also, co-workers and the nature of work were revealed to be the most significant factors that influenced the job satisfaction.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Satisfaction with job describes the situation of how an employed resident feels at work and performing work-related activities, i.e., expresses employee's satisfaction/dissatisfaction with paid work (Adomynienė & Gustainienė, 2011;Viningienė, 2014;Agha et al, 2017;Yeh & Hsieh, 2017;Ranaweera & Li, 2018;Randhawa & Narang, 2018;Crespi-Vallbona & Mascarilla-Miró, 2018;Mohammad et al, 2018;etc.). In addition, satisfaction with personal life is defined as an employee's emotional reaction to his life, i.e., all related areas, except workrelated activities (Makabe et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The review of the literature indicates that job satisfaction is multidimensional and includes facets such as fringe benefits, pay, promotion opportunities, supervision, organisational policies and procedures, co-workers, communication and the nature of the work (Ranaweera & Li 2018, Spector 1997. Hart (2014) and Jerome (2017) emphasised that employees' job satisfaction is the key to improving both organisational and individual performance and service quality, and that librarians who have a high level of job satisfaction for extended periods are more likely not to consider leaving the organisation.…”
Section: Personal Determinants Influencing Turnover Intentionmentioning
confidence: 99%